Occurrence of Lobotes surinamensis (Osteichthyes: Lobotidae) in the Mediterranean: Historical and recent data. Issue 1 (2nd January 2017) - Bilge, Gökçen; Filiz, Halit; Gülşahin, Anil
Abstract : This paper provides a review of the current status and historical distribution of Lobotes surinamensis in the Mediterranean Sea. Thirty two records were compiled for the period between 1968 and 2016, which shows that the species is in the Mediterranean much more abundant than previously understood.